The methodology of assessment of the brand strategy of conditions the digital economy - Chukurna, O.P.; Kofman, V. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
The role of brand valuation as an intangible asset in the structure of enterprise assets is substantiated. The role of the brand as a marketing asset in the capitalization of the enterprise is indicated. Problems of practice of recognition, estimation, protection, revaluation of intangible assets and a brand in Ukraine in comparison with foreign approaches in this sphere are formulated. The main problems of implementing the brand valuation methodology in the practice of Ukrainian enterprises include the use of a standard valuation of intangible assets, the lack of a standard for valuation of intangible assets, as well as the lack of uniformity in approaches to the management of intangible assets in general and brands in particular. One of the serious problems is the lack of harmonization of terminology in the field of valuation of intangible assets with international valuation standards. It was substantiated the three most common methodological approaches to brand assessment: costly, comparative and profitable. The analysis showed that in the world practice it is accepted to use an income approach to brand valuation, in which the determination of value is based on the discounted value of cash flows. Applied examples of the application of this brand value assessment method are considered. Based on the brand assessment methods discussed above, a number of methods have been proposed that allow taking into account the shortcomings of generally accepted approaches. The following brand assessment methods are proposed, which can be implemented in the practice of 176 assessing local and global brands: a method for assessing the value of brands using points; method of calculating the book value of the brand and the cost of its replacement; brand value assessment method using market transactions; brand value index model.
Keywords: brand; evaluation; brand assessment methods; brand value index